Heterogeneous Nuclear Ribonucleoprotein L Interacts with the 3′ Border of the Internal Ribosomal Entry Site of Hepatitis C Virus - Hahm, Bumsuk (American Society for Microbiology, 1998)
Translation initiation of hepatitis C virus (HCV) RNA occurs by internal entry of a ribosome into the 5′ nontranslated region in a cap-independent manner. The HCV RNA sequence from about nucleotide 40 up to the N terminus of the coding sequence of the core protein is required for efficient internal initiation of translation, though the precise border of the HCV internal ribosomal entry site (IRES) has yet to be determined. Several cellular proteins have been proposed to direct HCV IRES-dependent translation by binding to the HCV IRES. Here we report on a novel cellular protein that specifically interacts with the 3′ border of the HCV IRES in the core-coding sequence. This protein with an apparent molecular mass of 68 kDa turned out to be heterogeneous nuclear ribonucleoprotein L (hnRNP L). The binding of hnRNP L to the HCV IRES correlates with the translational efficiencies of corresponding mRNAs. This finding suggests that hnRNP L may play an important role in the translation of HCV mRNA through the IRES element.